The role of digital literacy in mediating human capital e-readiness on the performance of coffee MSMEs in Yogyakarta - Rr. Chusnu Syarifa Diah Kusuma,; Ari Pradhanawati,; Ngatno,; Reni Shinta Dewi, (Technium Social Sciences Journal, 2024)
Digital marketing is becoming an important component for the success of MSMEs in facing competition in the digital era. However, many MSMEs in Yogyakarta still face challenges in adopting digital marketing strategies because of low digital literacy and human resource readiness (Human Capital e-Readiness). The study aimed to analyze the influence of digital literacy on MSME performance through the role of digital literacy as a mediating variable. Also, the study aimed to examine the relationship between Human Capital E-Readiness and MSME performance through digital literacy. This study used a quantitative explanatory approach. Its focus was on coffee MSMEs that actively use digital marketing. The sample consisted of 100 respondents who were selected using purposive sampling from the coffee MSMEs that use digital marketing. Data were collected through a questionnaire with a Likert scale to measure respondents' attitudes and perceptions of the phenomenon being studied. The data were analyzed using Smart PLS 3.0 using a path analysis model. The study indicates that Human Capital E-Readiness has a positive and significant effect on Digital Literacy with a path coefficient of 0.599, t-Statistics of 7.787, and P-Value of 0.00, which supports the first hypothesis. Furthermore, Human Capital E-Readiness has a positive and significant effect on Performance with a path coefficient of 0.366, t-Statistics of 4.731, and P-Value of 0.00, which supports the second hypothesis. However, the effect of Digital Literacy on Performance is insignificant (t-Statistics of 1.932 and P-value of 0.054), so the third hypothesis is rejected. Finally, although Human Capital E-Readiness has a positive effect on Performance through Digital Literacy, this effect is not significant (t-Statistics of 1.798 and P-Value of 0.073) and the fourth hypothesis is rejected. The study confirms that Human Capital E-Readiness plays an important role in improving Digital Literacy, which affects the Performance of coffee MSMEs in Yogyakarta.